Diagnosis and treatment of Ankyloglossia in pediatric patients: A narrative review (Research, Society and Development, 2023)
The objective was to describe the diagnosis and treatment of ankyloglossia in pediatric patients through a narrative literature review. The bibliographic survey was carried out through the periodic databases CAPES, PubMed, LILACS and SciELO, the filters applied were Portuguese, English and Spanish, articles published in the period from 2017 to 2023, totaling 56 articles selected. The results obtained in this narrative review observed that ankyloglossia is a change that affects the lingual frenulum, causing a limitation in tongue movements, which directly impacts some functions, swallowing, chewing, speaking and breastfeeding. Some studies report that this condition may have genetic origins, associated with the autosomal dominant or recessive X chromosome. Its prevalence in newborns varies from 4% to 16%. Its diagnosis is given through tests that evaluate the mother's complaints, including difficulties in breastfeeding, physical examinations and tongue positioning. Its treatment can be given conservatively, with speech therapist monitoring, or non-conservatively, which consists of surgical intervention. The conclusion of this narrative review addresses the consequences of ankyloglossia and the importance of early diagnosis, so that the most appropriate test can be chosen to determine the best form of treatment.